2021
DOI: 10.1016/j.acra.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Low-Dose Chest Computed Tomography and RT-PCR Results for the Diagnosis of COVID-19: A Report of 27,824 Cases in Tehran, Iran

Abstract: Rationale and Objectives Real-time polymerase chain reaction (RT-PCR) remains the gold standard for confirmation of Coronavirus disease 2019 (COVID-19) despite having many disadvantages. Here, we investigated the diagnostic performance of chest computed tomography (CT) as an alternative to RT-PCR in patients with clinical suspicion of COVID-19 infection. Methods In this descriptive cross-sectional study, 27824 patients with clinical suspicion of COVID-19 infection who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…RT-PCR as a laboratory technique and confirmed one is not empty of false-negative reports according to numerous reasons ( 23 ). Therefore, in those highly suspicious patients with negative RT-PCR results, thin-section CT features could be considered as paramount guidance ( 10 , 24 , 25 ). On the other hand, according to seasonal climate changes, respiratory tract viruses such as influenza and respiratory syncytial viruses tend to involve bronchus, lung parenchyma, and also pleura.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR as a laboratory technique and confirmed one is not empty of false-negative reports according to numerous reasons ( 23 ). Therefore, in those highly suspicious patients with negative RT-PCR results, thin-section CT features could be considered as paramount guidance ( 10 , 24 , 25 ). On the other hand, according to seasonal climate changes, respiratory tract viruses such as influenza and respiratory syncytial viruses tend to involve bronchus, lung parenchyma, and also pleura.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, many researchers utilized the findings from medical imaging techniques (X-ray and computed tomography (CT)) to early diagnose the suspected COVID-19 cases and other lung diseases as well [10] . In fact, these techniques, particularly CT, have demonstrated to be an effective and fast alternative to the RT-PCR with high detection accuracy [7] , [11] . In addition, imaging data can be stored for disease follow-up measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Zali et al reported that CT scans are safer, faster, and more reliable than RT‐PCR for the diagnosis of COVID‐19 in regions with a high prevalence of the disease 12 . Kayaaslan et al investigated the effectiveness of the second RT‐PCR test in patients with suspected COVID‐19 whose first test was negative.…”
Section: Introductionmentioning
confidence: 99%
“…Zali et al reported that CT scans are safer, faster, and more reliable than RT‐PCR for the diagnosis of COVID‐19 in regions with a high prevalence of the disease. 12 Kayaaslan et al investigated the effectiveness of the second RT‐PCR test in patients with suspected COVID‐19 whose first test was negative. As a result, they reported that the second RT‐PCR test was a waste of labor and time, its additional contribution to the first test was very low, and that it was costly.…”
Section: Introductionmentioning
confidence: 99%